Current clinical trials in paediatrics: Report of the ESPEN special interest group in paediatrics. (October 2018) - Eveleens, R.D.; Gerasimidis, K.; Chourdakis, M.; Huysentruyt, K.; Koletzko, B.; Hulst, J.M.; Joosten, K.F.M.
Summary: Background & aims: At the 38th annual ESPEN congress in The Hague, the Netherlands, the Special Interest Group (SIG) in Paediatrics presented data about current research activities in the field of paediatric nutrition which are performed worldwide and translated this to future research perspectives. Methods: Extensive search of all registered observational and interventional clinical trials in the databaseClinicalTrials.gov using the search terms: children nutrition, paediatrics nutrition and children feeding. Results: A total of 717 studies were found; 173 were duplicates and 114 included adult participants and were therefore excluded. Hence, 430 remained for analysis, of which 69% were randomized controlled trials. The most investigated research topic was nutrition in specific diseases (n = 98), followed by obesity (n = 92), and studies including premature infants (n = 48). The overall median estimated enrolment of children in the trials was 150 children [IQR 50–365]. There were 44 studies in which >1000 participants will be enrolled and six studies with >10, 000 participants. Studies including >1000 participants were primarily performed in North America (39%), Africa (27%), and Europe (16%). Conclusions: This SIG report showed that 430 clinical nutrition trials in paediatrics are registered and current research focusses primarily on specific diseases and obesity. The SIG paediatrics encourages future research to invest in well-controlled interventional trials.